Rancang Bangun Aplikasi Al Wirdul Jalil Berbasis Mobile - Hariman Bahtiar; Baiq Andriska Candra Permana; Maspuk Al Hamdani (Infotek: Jurnal Informatika dan Teknologi, 2021)
Wirdul jalil is a collection of prayers and dhikr compiled by TGH. Afifudin Adnan is a student of Mawlanasysyaikh Tuan Guru Kyai Hajji Muhammad Zainuddin Abdul Madjid and also the founder of the Al Mukhtariyah Al Islamiyah Foundation. Wirdul jalil has become compulsory reading for congregations and students of the Al Mukhtariah Al Islamiyah Foundation and almost every year, the Al Mukhtariyah Al Islamiyah Islamic boarding school prints wirdul jalil. Then it was distributed to students and the congregation of Al Mukhtariyah Al Islmiyah to replace wirdul that had been damaged by age or lost. With the above problems, the author intends to design and build a mobile application that can produce jam'ah and students of the Al Mukhtariah Al Islamiyah Foundation in getting wirdul jalil without having to print it first, with this application congregations and students of the Al Mukhtariah Al Foundation Islamiyah can install it on a mobile device. That way, the congregation and students can read Wirdul Jalil practically on their mobile devices, and in the end the application can be used further.